Evaluation of rbc membrane stabilization and antioxidant activity of bombax ceiba in an in vitro method - N.SAMPATH KUMAR (International Journal of Pharma and Bio Sciences, 2011)
This study reports the human red blood cells (HRBC) and sheep red blood cells (SRBC) membrane stabilizing property and the antioxidizing property of ethyl acetate soluble fraction of the gynaceum part of Bombax ceiba. The probable mode by which Bombax ceiba mediates its effects on inflammatory conditions was studied on HRBC & SRBC exposed to hypotonic solution. The results of the study revealed that the EtOAc soluble fraction of Bombax ceiba possesses anti-inflammatory property. However, the extract did not have the membrane stabilizing property. The results of the study suggest that the antiinflammatory activity may not be related to membrane stabilization. It failed to show inhibition nature even in the higher concentration during the estimation antioxidizing property.